Risk of Fetal Loss After Chorionic Villus Sampling in Twin Pregnancy Derived From Propensity Score Matching Analysis. Issue 8 (August 2022) - Gil, M. M.; Rodríguez-Fernández, M.; Elger, T.; Akolekar, R.; Syngelaki, A.; Matallana, C. De Paco; Molina, F. S.; Arocena, M. Gallardo; Chaveeva, P.; Persico, N.; Accurti, V.; Kagan, K. O.; et al.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2022;59:162–168) Chorionic villus sampling (CVS) and its procedure-related risk of fetal loss in twin pregnancy have not been investigated in a randomized controlled trial setting. Authors of previous studies have concluded that only investigation of low-risk pregnancies could demonstrate the true effect of CVS.